2017
DOI: 10.1103/physrevb.96.125405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in heterostructures of transition metal dichalcogenides and graphene

Abstract: We use a van der Waals pickup technique to fabricate different heterostructures containing WSe 2 (WS 2 ) and graphene. The heterostructures were structured by plasma etching, contacted by one-dimensional edge contacts, and a top gate was deposited. For graphene/WSe 2 /SiO 2 samples we observe mobilities of ∼12 000 cm 2 V −1 s −1 . Magnetic-field-dependent resistance measurements on these samples show a peak in the conductivity at low magnetic fields. This dip is attributed to the weak antilocalization (WAL) ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 30 publications
(47 reference statements)
1
74
2
Order By: Relevance
“…Central to the derivation of the quantum kinetic equation for the reduced spin den-sity matrix [Eq. (13)] is the assumption of Gaussian disorder. The latter is equivalent to the first Born approximation [53] and thus it neglects any effects from skew scattering (allowed in the C 3v model [28]) and modifications to the energy dependence of the collision integral due to scattering resonances.…”
Section: Formalism: Spin Bloch Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Central to the derivation of the quantum kinetic equation for the reduced spin den-sity matrix [Eq. (13)] is the assumption of Gaussian disorder. The latter is equivalent to the first Born approximation [53] and thus it neglects any effects from skew scattering (allowed in the C 3v model [28]) and modifications to the energy dependence of the collision integral due to scattering resonances.…”
Section: Formalism: Spin Bloch Equationsmentioning
confidence: 99%
“…Next, we use the quantum kinetic equation Eq. (13) to obtain the spin Bloch equations governing the spin dynamics. Firstly, we separate the collision integral I[S κ k ] into intra and inter-valley parts, κ = {κ,κ} = {κ, −κ}, with the corresponding matrix elements of the scattering potential…”
Section: Formalism: Spin Bloch Equationsmentioning
confidence: 99%
“…These heterostructures can posses functionalities that the individual constituent layers may not have. In order to increase the SOC in graphene, one of the most actively pursued directions is to interface it with materials that have strong intrinsic SOC, such as transition metal dichalcogenides (TMDCs) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . TMDCs are expected to be good candidates for graphene spintronics for two reasons: i) it was shown that TMDC substrates do not degrade the mobility of graphene 23,26 , and ii) they host a strong intrinsic SOC of the order of 100 meV (10 meV) in their valence (conduction) band 27 and hence can potentially be suitable materials for proximity induced SOC.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to graphene/TMDC heterostructures, this approach has proven to be highly successful: measurements of weak antilocalization (WAL) indicate enhanced SOC in the graphene layer [6][7][8][9][10][11][12]; spin switches have been realized based on spin absorption in the TMDC layer [13,14]; predictions of giant spin relaxation anisotropy [15], which may be useful for orientation-dependent spin filtering, have been subsequently confirmed by experiments [16,17]; and recent measurements have indicated sizable charge-tospin conversion in the graphene layer [18,19]. Giant spin lifetime anisotropy has also been predicted in graphene/TI heterostructures [20], and recent measurements of spin transport and WAL have suggested that TIs also induce strong SOC in graphene [21,22].…”
Section: Introductionmentioning
confidence: 99%